2020
DOI: 10.21203/rs.3.rs-52431/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Echocardiographic patterns in critically ill COVID-19 patients.

Abstract: Background: Need for catecholamines is frequent in COVID-19 patients, but the main echocardiographic patterns are unknown. The objective was to report the main echo patterns in critically-ill COVID-19 patients. Methods: Observational and descriptive study in consecutive COVID-19 patients admitted to the ICU between March 12 and May 8, 2020. Systematic critical care echocardiography (CCE) was performed and retrospectively analyzed off-line. Echo values are reported in the overall population and in patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Pulmonary vascular dysfunction has been implicated in their pathophysiology (6, 7), and myocardial injury is a poor prognostic sign (8, 9). However, few studies have reported on right heart function in these patients and those that have tend to look at mixed cohorts of illness severity rather those mechanically ventilated with ARDS (10–12).…”
mentioning
confidence: 99%
“…Pulmonary vascular dysfunction has been implicated in their pathophysiology (6, 7), and myocardial injury is a poor prognostic sign (8, 9). However, few studies have reported on right heart function in these patients and those that have tend to look at mixed cohorts of illness severity rather those mechanically ventilated with ARDS (10–12).…”
mentioning
confidence: 99%